TERRESTRIAL RADIONUCLIDES IN SURFACE (DAM) WATER AND CONCOMITANT DOSE IN METROPOLITAN KUALA LUMPUR - Khandaker, Mayeen Uddin; Uwatse, Onosohwo Bemigho; Bin Shamsul Khairi, Khairi Azri; Faruque, M R I; Bradley, D A (Radiation protection dosimetry, 2019)
Abstract Batu Dam is of considerable importance to the metropolis of Kuala Lumpur, its existence and the quality assessment of its waters being essential in helping to maintain the lives of a large sector of the Malaysian population. Concerning the level of naturally occurring radioactivity contained within its waters, a well characterised HPGe γ-ray technique has been used in making measurements of the concentrations of primordial radionuclides in samples of surface water from the Dam. Based on the mean individual daily consumption of dam water, estimation has been made of the concomitant radiation dose. Activity concentrations, in units of Bq l−1, have been found to be in the range 2.4–3.2 for 226Ra, 1.1–1.3 for 232Th and 22.7–40.7 for 40K, in line with literature data for surface waters. The total annual ingestion dose for infants (<1 y) and adolescents (12–17 y) are found to be significant and greater than the World Health Organization recommended maximum dose of 0.1 mSv y−1 from the imbibing of drinking water. However, the Dam water does not pose a threat to public health, the Dam water not being used as the sole source of drinking water. Noting that this is the only known study of water from Batu Dam, the reported levels allow for evaluation of future changes in the natural radioactivity profile.